Goal Orientation, Ketangguhan Mental, Dan Prestasi Akademik Student Athlete - Husain Albaar Ahmad (Psychological Journal: Science and Practice, 2023)
Academic achievement is an important component in education as a condition for knowing how much competent person. Like student athletes who are carrying out their education at a university, they carry out training tasks as an athlete and study as a student so that there are stereotypes about success and academic failure. This study aimed to determine the effect of mental toughness on academic achievement of student athlete, knowing the effect of goal orientation on student athlete academic achievement, and also determine whether there is an interaction between mental toughness and goal orientation. Number of subjects in the study 113 student athletes. The instruments used were the Mental Toughness Index and Achievement Goals Scales. The results showed that goal orientation was related to academic achievement (β = 0.004; r = 0.043), mental toughness had no effect on academic achievement (β = -0.005; r = 0.057), and was not found the interaction between mental toughness and goal orientation in predicting academic achievement (β = 0.000; r = 0.061).